1981
DOI: 10.1007/bf00038794
|View full text |Cite
|
Sign up to set email alerts
|

The location and characteristics of novel sources of resistance to Bremia Lactucae Regel (downy mildew) in wild Lactuca L. Species

Abstract: Twenty-one accessions of 3 wild Lacfuca species which could be hybridised with L. sativa, the cultivated lettuce, were inoculated at different stages of plant development with 3 multivirulent isolates of Bremia lactucae.Nineteen sources of resistance to B. lactucae, not attributable to the previously recognised resistance factors l-l 1 were identified. Two lines of L. serriola showed similar resistance patterns as lines carrying Rl 1. The resistance of some accession was incomplete particularly at the seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…Some other R-factors were not assigned to a linkage group (Table 5). From other studies (Lebeda, 1983(Lebeda, , 1986Norwood et al, 1981;Bonnier et al, 1992) it is evident that numerous additional resistance genes might be present in L. serriola accessions. The occurrence of race-specificity will also probably be a very common phenomenon in the L. serriola -B. lactucae pathosystem (Lebeda, 1984b(Lebeda, , 1986Lebeda and Petrželová, 2001).…”
Section: Resistance Mechanisms Of Wild Lactuca Sppmentioning
confidence: 96%
See 2 more Smart Citations
“…Some other R-factors were not assigned to a linkage group (Table 5). From other studies (Lebeda, 1983(Lebeda, , 1986Norwood et al, 1981;Bonnier et al, 1992) it is evident that numerous additional resistance genes might be present in L. serriola accessions. The occurrence of race-specificity will also probably be a very common phenomenon in the L. serriola -B. lactucae pathosystem (Lebeda, 1984b(Lebeda, , 1986Lebeda and Petrželová, 2001).…”
Section: Resistance Mechanisms Of Wild Lactuca Sppmentioning
confidence: 96%
“…Norwood et al (1981) found that it was not possible to clearly interpret the segregation data from progeny because of the sparse sporulation, frequent occurrence of necrosis and difficulty in classifying the infected seedlings into discrete categories. Current thoughts are that this resistance is based on some major gene(s) and modifiers (Table 5).…”
Section: Race-nonspecific Resistancementioning
confidence: 96%
See 1 more Smart Citation
“…The broad resistance spectrum of L. saligna was described in a couple of studies since 1976 (Netzer et al 1976;Norwood et al 1981;Bonnier et al 1992), but has not been graphically visualized. To illustrate the host and nonhost classification in Lactuca species, we have visualized a large dataset obtained from the Dutch Centre for Genetic Resources (CGN) of 55 four Lactuca species and their B. lactucae infection scores at seedling stage, supplemented with some seedling disease test data for three accessions not tested by CGN.…”
Section: Host-nonhost Classificationmentioning
confidence: 99%
“…The cultivated host species L. sativa is cross-compatible with the nonhost species L. saligna. Since 1976, several studies indicate that L. saligna accessions are totally disease-free (Netzer et al, 1976;Norwood et al, 1981;Lebeda, 1986;Gustafsson, 1989;Bonnier et al, 1992;Petrželová et al, 2011;Van Treuren et al, 2011). Histology studies suggested that germinated conidia in L. saligna were arrested before normal hyphae formation (Lebeda et al, 2008;Zhang et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%